Identification of metabolic pathways modulated by GAM and NGAM in the inhibition of Staphylococcus aureus biofilm formation - Afsharnia, Amirmohammad; Nauta, Arjen; Groeneveld, Andre; Fernandez-Ciruelos, Blanca; Asadpoor, Mostafa; Folkerts, Gert; Braber, Saskia; Wösten, Marc (Frontiers in Microbiology, 2025)
The prevalence of antibiotic-resistant bacterial strains, particularly Staphylococcus aureus, poses a significant threat to global health. The ability of S. aureus to form biofilms reduces the efficacy of antibiotics. Therefore, the need for innovative anti-biofilm strategies to improve the efficacy of antibiotic therapy is crucial, particularly when biofilms cause treatment failure. In this study, we investigated the effects of glucosamine (GAM) and its acetylated derivative, N-acetylglucosamine (NGAM), on the biofilm formation of the multidrug-resistant S. aureus strain Wood 46. The minimum biofilm inhibitory concentration (MBIC) assay was used to evaluate the inhibition of biofilm formation. The results indicated that 2–8% of GAM significantly inhibited S. aureus biofilm formation. However, only a high concentration of NGAM (8%) showed partial inhibition of biofilm formation. The RNA sequencing analysis of the treated biofilms indicated that, compared to NGAM, GAM leads to a more pronounced downregulation of S. aureus adhesion genes (eno, ebps, and sraP) and genes involved in arginine biosynthesis and tricarboxylic acid (TCA) pathways, which are essential for biofilm proteinaceous structure. The decreased pH in the biofilm environment treated with higher GAM concentrations supports its observed anti-biofilm activity and is likely linked to impaired pH homeostasis resulting from the downregulation of ureABC genes and disruption of urea metabolism, a process interconnected with arginine biosynthesis. In conclusion, unlike its acetylated form (NGAM), GAM is a potent anti-biofilm agent that effectively inhibits the biofilm formation of S. aureus Wood 46 and significantly alters the gene expression profile associated with biofilm formation.